Moisture protection of structures adjacent to the ground in historic buildings - Semko, Oleksandr; Filonenko, Olena; Yurin, Oleg; Mahas, Nataliia; Rudenko, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2022)
Vertical and horizontal waterproofing of such underground structures has either been absent since the time of construction, or has already lost its operational characteristics. Moisture from the soil rises through the capillaries of the brickwork, which leads to the destruction of the brick and the finishing layer, the appearance of fungi and mold on the surfaces. Constant wetting of structures bordering the ground leads to a decrease in thermal properties, wear of building structures and a decrease in the standard service life of houses. In most cases, the development of restoration measures involves antiseptic treatment and replacement of wall surface finishes. Such activities carried out repair work in the building of the lyceum in Poltava. The paper emphasizes the introduction of comprehensive measures to restore vertical and horizontal waterproofing on the example of a real object of a gymnasium building in the Poltava region. The damage to the enclosing structures of the basement floor of the gymnasium building and the reasons for their occurrence were analyzed. Measures are proposed to ensure further trouble-free operation of structures adjacent to the ground.